NEW SPECIES OF BAMBOOS (POACEAE-BAMBUSOIDEAE) FROM BALI - Elizabeth Anita Widjaja; Inggit Pudji Astuti; Ida Bagus Ketut Arinasa (Research Center for Biology, 2004)
WIDJAJA, E.A., ASTUTI, I. P., ARINASA, I. B. K. 2004. New species of bamboos (Poaceae-Bambusoideae) from Bali. Reinwardtia 12(2):199 - 204. Five new species of bamboos from Bali are described: Bambusa ooh, Dinochloa sepang, Gigantochloa aya, Gigantochloa baliana and Gigantochloa taluh in the context of a proposal field guide to Balinese bamboos. Description including the distribution and the vernacular names are provided.